Determination of oxidant stress in plasma of rheumatoid arthritis and primary osteoarthritis patients - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2010)
Determination of oxidant stress in plasma of rheumatoid arthritis (RA) and primary osteoarthritis (POA) patients is important in understanding the pathogenesis of these diseases. In this study, we examined the relationship between oxidant stress and inflammation by measuring protein carbonyl content, thiol levels and plasma protein fractions as the oxidation markers and erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) tests as inflammation markers. Protein carbonyls content was higher in RA and POA patients, as compared to controls (p < 0.0001), while the plasma thiol levels in both groups of patients were significantly lower than controls (p < 0.0001). Increased levels of proteins under 40 kDa molecular mass were detected in the RA and POA patients compared to that of controls (p < 0.0001) both in HPLC and SDS-PAGE analysis. Total protein concentration in plasma of RA patients was higher than the controls (p < 0.001), while in POA patients was lower than that of controls (p < 0.001). ESR and CRP levels were higher in both the patient groups than the normal group (p < 0.001). These results suggested that alterations in the oxidant stress markers could be the cause of inflammation in these diseases. Thus, while working for RA/POA treatment strategies, consideration of the relationship between oxidant stress and inflammation would be worth evaluating.
Keywords: Oxidative stress; Inflammation; Rheumatoid arthritis; Primary osteoarthritis; Biochemical markers; OXIDATIVE STRESS; LIPID-PEROXIDATION; PROTEIN OXIDATION; SERUM; DEGRADATION; EXPRESSION; CARTILAGE; DISEASE; DAMAGE